2008
DOI: 10.1111/j.1749-124x.2008.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Excess Liquidity and Inflation Dynamics in China: 1997–2007

Abstract: The surge in international capital inflows and the remarkable excess liquidity in China between 1997 and 2007 are examined in the present paper. It is shown that China's improved position in terms of foreign exchange purchases, ignited by huge foreign capital inflows, has effectively induced excess liquidity in China. More importantly, by developing an econometric model for inflation and excess liquidity, the present study demonstrates that excess liquidity has imposed significant pressure on inflation in Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Some economists confirmed this causation using sophisticated quantitative frameworks. For instances, Zhang and Pang (2008), applying quarterly data between 1997 and 2007, concluded that excess liquidity had systematically imposed pressures on inflation. Likewise, Zhang (2009) showed that excess liquidity, ignited by dramatic capital inflows, was a significant driver for consumer price inflation in China during 1998China during -2007 But academic findings have not been consistent and uniform.…”
Section: The Hypothesesmentioning
confidence: 97%
“…Some economists confirmed this causation using sophisticated quantitative frameworks. For instances, Zhang and Pang (2008), applying quarterly data between 1997 and 2007, concluded that excess liquidity had systematically imposed pressures on inflation. Likewise, Zhang (2009) showed that excess liquidity, ignited by dramatic capital inflows, was a significant driver for consumer price inflation in China during 1998China during -2007 But academic findings have not been consistent and uniform.…”
Section: The Hypothesesmentioning
confidence: 97%
“…Most of the studies under the 'impact' area pay great attention to inflation and asset price bubbles and find empirical evidence that excess liquidity (indexed by the ratio of money supply M2 to nominal GDP (M2/NGDP) imposes significant pressure on the consumer price index (CPI) in China (Guo & Li, 2011;Huang et al, 2010;Yang, 2010;Zhang, 2009;Zhang & Pang, 2008). Mehrotra (2008) finds that excess liquidity pushes up not only price inflation but also output.…”
Section: The Effects Of Excess Reservementioning
confidence: 98%
“…Another issue that merits future attention is the measure of excess liquidity in the overall economy. The current literature defines excess liquidity as the gap between the growth rate of the money supply (M2) and nominal GDP (Guo & Li, 2011;Yang, 2010), or the deviation of ratio of M2 and nominal GDP from their long-term trends (Huang et al, 2010;Zhang, 2009;Zhang & Pang, 2008). It is crucial to take not only economic growth but also the interest rate into the measure of long-term excess liquidity because the interest rate may induce variations in the output-velocity of money and complicate the link between standard monetary aggregates and prices (Orphanides & Porter, 2000); hence, the money demand will be altered according to price changes and so will the excess liquidity (Berger & Harjes, 2009).…”
Section: Excess Reserve Sourcesmentioning
confidence: 99%
“…The aggregate excess reserves beyond statutory requirements in Chinese banking system stood at an average of 10% of deposit base in the 1990s and the early 2000s (Anderson, 2009;Laurens & Maino, 2009), although the ratio gradually fell to 3.3% in 2012, 2 yet it is considered to be high compared to banks in the US and Euro-zone countries and higher than the levels maintained for precautionary purposes (Anderson, 2009;Ma, Yan, & Liu, 2011;Wei, Pan, Yang, Zhang, & Chen, 2008). The large involuntary excess reserves in the Chinese banking system have raised some concerns regarding the forming of the price bubble which may lead to financial crisis (Guo & Li, 2011;Huang, Wang, & Hua, 2010;Yang, 2010;Zhang, 2009;Zhang & Pang, 2008). The presence of involuntary excess reserves indicates unwanted surplus liquidity (Agenor, Aizenman, & Hoffmaister, 2004).…”
Section: Introductionmentioning
confidence: 95%